Tecnologia eletroquímica como tratamento alternativo de efluentes têxteis sintéticos utilizando ânodos de platina e diamante - Rocha, Jéssica Horacina Bezerra (2011)
In this work, the treatment of synthetic wastewaters containing Remazol Red BR (RRB) and Novacron Blue C-D (NB) by anodic oxidation using boron doped diamond anodes (BDD) and Novacron Yellow (YN) using BDD and Platinum (Pt) anodes was investigated. Galvanostatic electrolyses of RRB and NB synthetic wastewaters have led to the complete decolorization removal at different operating conditions (current density, pH and temperature). The influence of these parameters was investigated in order to find the best conditions for dyestuff colour removal. According to the experimental results obtained, the electrochemical oxidation process is suitable for decolorizing wastewaters containing these textile dyes, due to the electrocatalytic properties of BDD and Pt anode. Energy requirements for removing colour during galvanostatic electrolyses of RRB, NB and YN synthetic solutions depends mainly on the operating conditions; for example for RRB, it passes from 3.30 kWh m-3 at 20 mA cm-2 to 4.28 kWh m-3 at 60 mA cm-2 (pH = 1); 15.23 kWh m-3 at 20 mA cm-2 to 24.75 kWh m-3 at 60 mA cm-2 (pH = 4.5); 10.80 kWh m-3 at 20 mA cm-2 to 31.5 kWh m-3 at 60 mA cm-2 (pH = 8) (data estimated per volume of treated effluent). In order to verify the Brazilian law regulations of NB and RRB synthetic solutions after electrochemical decolourisation treatment, Hazen Units values were determined and the total colour removal was achieved; remaining into the regulations. Finally, electrical energy cost for removing colour was estimated